"DNA chip" technology developed for detecting food-borne pathogens. Issue 7 (July 2015) - Unknown
Abstract : In Japan, Toshiba Ltd and Kawasaki City Institute for Public Health are collaborating on the development of a rapid and efficient "DNA chip" technology for detecting major types of food-borne pathogens.